PROBLEM SOLVING & LEARNING STYLE OF MEMORIZER “AL QURAN” TOWARD UNDERSTANDING OF MATHEMATIC - Wandini, Rora Rizky; Damanik, Emeliya Sukma Dara; Daulay, Sholihatul Hamidah (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
There are several theories about the classification of learning styles as expressed by De Poter & Henacki (visual, auditory and kinesthetic) and Felder & Silverman. This study focuses on analyzing the learning styles of students who have memorized the Koran mutqin toward their understanding about the concept of multiplication. This study used a descriptive quantitative research approach. The total number of participants are 110 students and divided them into two parts; students memorizing the Koran around 5 juz (9-12 years) and 55 students who did not memorize the Koran. Researchers used purposive sampling technique in determining the participants. The determination of the learning style, researcher took from theory (Felder & Silvermen), and the researcher's learning style using a questionnaire in grouping. The results of this study identified that {1} students who have memorized 5 juz tend to use active-reflective learning style and they have a good understanding of the concept of multiplication reach 63.2%, while students who did not memorize the Koran, they have the similar learning style were categorized into sufficient and reach 50.5% {2} Students who memorized the Qur'an 5 juz tend to use the sensing-intuitive learning style had a good understanding into 70.8%. Meanwhile, students who did not memorize the Koran and had the same learning dimensions were indicated into good category reach percentage into 60, 8% {3} Students who memorized the Qur'an 5 juz, they tend to use visualverbal intervention and had a good understanding to the concept of multiplication reach 73.3%. Meanwhile, children who did not memorize the Koran, they got percentage in 58.9% { 4} There are no students who have memorization of the Qur'an 5 are included in the sequential-global style. Therefore, there is no test but researcher found that students who do not memorize the Koran tend to use sequential-global style included to less category shows percentage in 40.6%.